Beyond the Surface: Investigating Clinical and Magnetic Resonance Imaging Dynamics in Knee Injuries: A Cross-sectional Study - Gaurav Singh; Vineet Kumar; Swagat Mahapatra; Pankaj Aggarwal; Ammar Mohd. Aslam; Prabhat Pandey; Prakhar Mishra (Journal of Orthopedics, Traumatology and Rehabilitation)
Context: Orthopedic surgeons frequently encounter knee soft tissue injuries such as meniscal and ligament injuries. This study seeks to explore the diagnostic efficacy of clinical examination, magnetic resonance imaging (MRI), and arthroscopy in identifying knee injuries. Subjects and Methods: This prospective observational study enrolled 120 patients with knee injuries slated for arthroscopic surgery based on clinical and MRI assessments. The study assessed and compared the diagnostic accuracy of clinical and MRI findings. Statistical Analysis Used: Statistical analysis was performed using SPSS software (SPSS Inc., Chicago, IL, USA) for the Windows program (21.0 version). The Spearman correlation analysis was done to assess the relationship between the various parameters. The level of agreement was assessed using Cohen’s kappa statistics. Interpretation of kappa statistics is as follows: 0 to 0.20-Slight agreement; 0.1 to 0.39-Fair; 0.40 to 0.59-Moderate; 0.60 to 0.79- Substantial and 0.80 to 0.90-Almost perfect agreement. Sensitivity, specificity, accuracy, positive predictive value and negative predictive value were calculated and observed by using 2 × 2 contingency table. P < 0.05 was considered statistically significant. Results: When comparing MRI and arthroscopy findings, the anterior cruciate ligament (ACL) tear exhibited the highest sensitivity and specificity at 100.00% and 91.84%, respectively, while the medial meniscus tear had the lowest sensitivity and specificity at 80.23% and 61.76%. Regarding the comparison between clinical examination and arthroscopy, the Lachman test displayed the highest sensitivity at 95.92%, whereas McMurray’s test (Lateral Meniscus) had the lowest sensitivity at 54.55%, and the posterior Drawer’s test showed the lowest specificity at 60.00%. Lachman also demonstrated the highest diagnostic accuracy at 98.33%, while the posterior Drawer’s test had the lowest diagnostic accuracy at 70.00%. Conclusions: Despite a few limitations, clinical examination and MRI currently stand out as the most precise non-invasive methods for detecting abnormalities in the menisci and the ACL. These diagnostic approaches provide valuable insights into the structural integrity of these knee components, allowing for a comprehensive assessment without the need for invasive procedures.